2012
DOI: 10.1111/j.1749-771x.2011.01133.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors of catheter‐associated urinary tract infection in Yazd – Iran

Abstract: Catheter‐associated urinary tract infection (CAUTI) is the most common nosocomial infection, accounting for more than 1 million cases each year in the US hospitals and nursing homes. The significant number of infections and dissemination of resistant bacteria in hospitals make it important to find ways to decrease their incidence. The aim of the study was to describe the incidence and risk factors of CAUTIs. A cohort study was conducted from 2003 to 2008 on every patient who became catheterized consecutively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 20 publications
1
5
1
Order By: Relevance
“…Not surprisingly, we found that more than 60year-old have more risk to suffer from catheterassociated urinary tract infection. It is consistent with theories of immunosenescence [22] and the previous study [21] with cohort study that high rates catheterassociated urinary tract infection in elderly patients with average age 64.6 years.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Not surprisingly, we found that more than 60year-old have more risk to suffer from catheterassociated urinary tract infection. It is consistent with theories of immunosenescence [22] and the previous study [21] with cohort study that high rates catheterassociated urinary tract infection in elderly patients with average age 64.6 years.…”
Section: Discussionsupporting
confidence: 91%
“…Duration of catheterisation was the most influential independent factor with catheter-associated urinary tract infection. It has been shown in another study [21], [28], [29]. The odds of the duration of catheterisation 32.85 higher for a patient who inserted a catheter for five days or more.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Risk factors associated with the development of CAUTI include female gender, age, impaired immunity, co-morbidity, and increased duration of catheterization [6]. On the contrary, our study found no significant association of CAUTI with age, gender, and BMI.…”
Section: Job Et Alcontrasting
confidence: 92%
“…Risk factors in the development of a CAUTI identified so far are female gender, obesity, immune deficiency, duration of catheter use, length of hospital stay, and unnecessary placement of urinary catheters [6]. Duration of catheterization remains a significant factor in predicting CAUTI and each day of catheterization increases the risk of CAUTI by 3-10% [7].…”
Section: Introductionmentioning
confidence: 99%